2021
DOI: 10.1002/bab.2111
|View full text |Cite
|
Sign up to set email alerts
|

Glutamine alleviates the renal dysfunction associated with gentamicin‐induced acute kidney injury in Sprague–Dawley rats

Abstract: Sepsis is a clinical condition caused by an uncontrolled response to an infection, leading to acute kidney injury (AKI) and an increased risk of mortality. Although life support and antibiotic therapy are available, the mortality rate remains high in patients with sepsis. The present study investigated the therapeutic effect of glutamine on gentamicin-induced acute kidney injury in Sprague-Dawley rats. We randomly grouped 24 male rats to the normal control, AKI (control), glutamine 50 mg/kg, and glutamine 500 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…16 Mediating inflammation and OS is regarded as one of the main strategies in treating sepsis-related AKI. 17,18 This article focused on the influence of OS and pro-inflammatory cytokine response post-AKI and explored the inflammatory mechanism of kidney injury. It was found that the natural compound ANE displayed a renal protective function through AMPK/Sirt-1 signaling pathway activation to mitigate OS and inflammatory response.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…16 Mediating inflammation and OS is regarded as one of the main strategies in treating sepsis-related AKI. 17,18 This article focused on the influence of OS and pro-inflammatory cytokine response post-AKI and explored the inflammatory mechanism of kidney injury. It was found that the natural compound ANE displayed a renal protective function through AMPK/Sirt-1 signaling pathway activation to mitigate OS and inflammatory response.…”
Section: Discussionmentioning
confidence: 99%
“…Additional methods that may be used to treat sepsis after AKI could include reducing certain metabolites, cytokines, or harmful molecules that affect immunity, as well as avoiding excessive fluid intake and the unnecessary use of catheter insertion 16 . Mediating inflammation and OS is regarded as one of the main strategies in treating sepsis‐related AKI 17,18 . This article focused on the influence of OS and pro‐inflammatory cytokine response post‐AKI and explored the inflammatory mechanism of kidney injury.…”
Section: Discussionmentioning
confidence: 99%
“…GLN supplementation was protective in gentamicin AKI by increasing catalase, superoxide dismutase, glutathione peroxidase, and glutathione levels [82]. GLN administration 30 min before acetaminophen protected renal function [83].…”
Section: Glutamine-renal Protectionmentioning
confidence: 93%
“…Experimental studies have shown that administering GLN supplements has significant impacts, particularly in I/R cardiac and renal injury. GLN has been found to maintain myocardial tissue metabolism, ATP levels, and reduced GSH levels [56,60,61,82]. It also stimulates the synthesis of heat shock proteins [56,58,59,66] and replenishes α-KG in the Krebs cycle [8,61].…”
Section: Glutamine In Cardiac Surgery-the Clinical Experiencementioning
confidence: 99%
“…In addition, there was concomitant damage to renal tubular epithelial cells and blood vessels, as well as a strong inflammatory response [ 6 , 7 ]. Recent studies have found that glutamine, a drug used as a conventional nutritional therapy for AKI, could protect the kidney by reducing oxidative stress [ 8 , 9 ]. Under certain physiological circumstances, glutamine is widely used as a major metabolic fuel for the kidney and immune system [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%